Long-term light-curves of transient X-ray pulsars as a tool to study disk−magnetosphere interaction - Forsblom, Sofia (My University, 2022)
X-ray pulsars are highly magnetized neutron stars in close binary systems accreting matter from a normal companion star. Their strong magnetic fields channel the accreting matter onto the magnetic poles of the neutron star, releasing an enormous amount of energy in the form of X-rays. If the matter accreted from the stellar companion carries a large amount of angular momentum, it will generally form an accretion disk around the neutron star. The strong magnetic field of the neutron star will effectively truncate the accretion disk at the magnetospheric radius, which defines the space around the X-ray pulsar known as the magnetosphere. The observed behavior of the X-ray pulsar will depend on several factors, including the rate at which mass is being accreted. At low mass accretion rates, the magnetosphere will be able to extend further out, and if the mass accretion rate drops below some critical value, accreting matter will be stopped by the centrifugal barrier created by the neutron star’s rapidly spinning magnetosphere. This is known as the propeller effect, because matter is basically flung out by the rapidly spinning magnetosphere. The propeller effect is generally used to explain the declining phases of the outbursts of transient X-ray pulsars into quiescence. Another phenomenon recently proposed for transient X-ray pulsars is the possibility of accretion from a cold accretion disk at low mass accretion rates. This is caused by a thermal-viscous instability developing in the accretion disk and is commonly invoked to explain the characteristic outbursts of dwarf novae, where the theory is encapsulated in the disk instability model (DIM). During the decay of dwarf nova outbursts, a propagating cooling front will appear in the accretion disk, and when this front reaches the inner disk radius, the entire disk will be in a cold state of neutral hydrogen. In this thesis, the data from observations made by the Swift observatory have been analyzed with the intent to test the possibility of the appearance of a propagating cooling front during the decaying phases of the outbursts of transient X-ray pulsars. The light-curves of three sources (SMC X-2, 4U 0115+63, V 0332+53) were fitted with a smoothed spline representing the observed behavior, which was subsequently compared to the modeled luminosity decay caused by the propagation of a cooling front. The result of the analysis is that by modeling the expected behavior of a cooling front propagating through the accretion disk, the luminosity decay of these transient X-ray pulsar’s outbursts can be well explained without the need to invoke the propeller effect. Additionally, the obtained αcold values are consistent with the values commonly used in the DIM.
Keywords: neutron star, magnetic field, accretion, X-ray binaries